The Model of Heavy Industries Profitability (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to analyze the influence of cash turnover, receivebles turnover and sales on profitability of Astra International registered on Indonesian Stock Exchange within the time span of  eight years (2011 to 2018). Methods of data analysis using the classic assumption test, multiple linear regression analysis, F test, and t test. The Finding  of this study  were cash turnover, receivable turnover,and sales have  a simultaneously affect on profitability of Firm, Whereas  the two variables, cash turnover and sales had a partially positive affect on profitability  of Firm, Meanwhile  receivable turnover had a partially negative affect on profitability  of Firm. The implication of this study to the firm in facing challenging business conditions is to implement cost efficiency programs that emphasize various innovative steps and at the same time focus on the availability of distribution support, ease of access and guaranteed product and service quality for customers.